The borrowed life of Frederick Fife : a novel [large type] - Johnston, Anna, 1983- (HarperCollins Publishers, 2024)
"For readers of Remarkably Bright Creatures and The Pilgrimage of Harold Frye, a warm, life-affirming debut about a zany case of mistaken identity that allows a lonely old man one last chance to be part of a family. "Would you mind terribly, old boy, if I borrowed the rest of your life? I promise I'll take excellent care of it." Frederick Fife was born with an extra helping of kindness in his heart. If he borrowed your car, he'd return it washed with a full tank of gas. The problem is there's nobody left in Fred's life to borrow from. At eighty-two, he's desperately lonely, broke, and on the brink of homelessness. Fred's luck changes when, in a bizarre case of mistaken identity, he takes the place of Bernard Greer at the local nursing home. Now he has a roof over his head, three meals a day, and, most importantly, the chance to be part of a family again. All he has to do is hope that his poker face is in better shape than his prostate and that his look-alike never turns up. As Fred navigates life in Bernard's shoes, he learns about the man's past and what it might take to return a life in better condition than he found it. Bittersweet and remarkably perceptive, The Borrowed Life of Frederick Fife is a feel-good, clever novel about grief, forgiveness, redemption, and finding family, from an exciting new voice in fiction"--